Primary familial brain calcification in the 'IBGC2' kindred: All linkage roads lead to SLC20A2. Issue 12 (27th September 2016) - Grütz, Karen; Volpato, Claudia B.; Domingo, Aloysius; Alvarez‐Fischer, Daniel; Gebert, Uwe; Schifferle, Günther; Buffone, Ebba; Wszolek, Zbigniew K.; Rademakers, Rosa; Ferbert, Andreas; Hicks, Andrew A.; Klein, Christine; et al.
ABSTRACT: Background: Linkage analyses of families with primary familial brain calcification (formerly idiopathic basal ganglia calcification [IBGC]) identified 3 candidate loci (IBGC1‐3). Recently, SLC20A2 mutations were found in the IBGC1 and IBGC3 families, merging these 2 loci. We here elucidate the genetic cause of primary familial brain calcification in the 'IBGC2' kindred. Methods: We sequenced known primary familial brain calcification genes and quantified SLC20A2 and PDGFB . Moreover, CT scans of affected and unaffected family members were evaluated by 2 blinded neuroradiologists for distribution of brain calcification. Results: A heterozygous multiexonic SLC20A2 deletion was detected in several affected family members. A reevaluation of neuroimaging data revealed a subset of mutation‐negative individuals with only mild and/or unilateral calcification. Conclusions: The identified SLC20A2 mutation resolves the genetic cause of primary familial brain calcification in the 'IBGC2' kindred, collapsing 'IBGC2' into IBGC1. We suggest an algorithm for predicting the chances of finding genetic mutations that has to be validated in further studies. Our study enhances criteria for the evaluation of neuroimaging data, contributing further to the much needed harmonization of diagnostic and research data collection in primary familial brain calcification. © 2016 International Parkinson and Movement Disorder Society.